2017
DOI: 10.1038/s41598-017-05876-y
|View full text |Cite
|
Sign up to set email alerts
|

Snake venom VEGF Vammin induces a highly efficient angiogenic response in skeletal muscle via VEGFR-2/NRP specific signaling

Abstract: Vascular Endothelial Growth Factors (VEGFs) are promising molecules for the treatment of ischemic diseases by pro-angiogenic therapy. Snake venom VEGFs are a novel subgroup with unique receptor binding profiles and as such are potential new therapeutic agents. We determined the ligand-receptor interactions, gene regulation and angiogenic properties of Vipera ammodytes venom VEGF, Vammin, and compared it to the canonical angiogenic factor VEGF-A to evaluate the use of Vammin for therapeutic angiogenesis. Vammin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, snaclecs constituted nearly ~20% of the venom proteome of the Deccan Plateau (MP) population, whereas the Gangetic Plain (WB) and the Western Ghats (MH) populations contained only 5% and 2% of this toxin, respectively. While VEGF, a family of toxins responsible for inducing vascular permeability and lower blood pressure [ 39 , 40 ], was only identified in trace amounts in the other populations of D . russelii (<1%), it was found to constitute ~8% of the venom of the Deccan Plateau (MP) population ( S2 – S4 Tables).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, snaclecs constituted nearly ~20% of the venom proteome of the Deccan Plateau (MP) population, whereas the Gangetic Plain (WB) and the Western Ghats (MH) populations contained only 5% and 2% of this toxin, respectively. While VEGF, a family of toxins responsible for inducing vascular permeability and lower blood pressure [ 39 , 40 ], was only identified in trace amounts in the other populations of D . russelii (<1%), it was found to constitute ~8% of the venom of the Deccan Plateau (MP) population ( S2 – S4 Tables).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that different variants of snake venom VEGF induce angiogenesis and vascular permeability through different mechanisms [ 157 , 158 ]. Snake venom VEGF are potential candidates for therapeutic angiogenesis [ 159 ]. A low abundance of Kunitz type serine protease inhibitors (KSPI) was identified in the venom of both snakes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, vammin and VR-1, isolated from the venoms of Vipera ammodytes and Daboia russelii , respectively, bind only kinase insert domain receptor (KDR) with high affinity but not to other VEGF receptors [19]. It is known that the C-terminal regions of VEGFs are one of the determinants for receptor specificities [20,21]. Yamazaki et al [18] has also reported that svVEGF of P. flavoviridis preferentially binds to Flt-1 rather than to KDR, unlike vammin and VR-1 [22].…”
Section: Discussionmentioning
confidence: 99%